Por dentro da Gaiola de Faraday: estudos e ideias sobre a estrutura da matéria (1836-1838) - Leite, Rodrigo Pietro (2012)
This research deals with experimental practices developed by Michael Faraday, held from 1836 until early 1838, focusing mainly on the experiment, which would later be known as the "Faraday cage". We analyzed the Experimental Researches in Electricity (ERE), in which are recorded reflections and experiments that were subsequently presented to the Royal Society. We also analyzed part of his correspondence and his diary, and other works. This analysis confirmed that the pillars of thought Faraday were the idea of unity of natural forces and the proposed improvement of the mind. Michael Faraday conducted several experimental tests, which helped formulate concepts fundamental to the understanding of matter. In this study focused in particular experiments relating to the load charge distribution